Transformational leadership research : issues and implications - Pawar, Badrinarayan S. (Journal of organizational change management, 2004)
The new transformational leadership theories stress the emotional bond between leaders and followers, as opposed to the cognitivecalculative exchange emphasized by traditional transactional theories. However, very little empirical research has concentrated on the effects of transformational leaders on emotion- versus cognition-focused aspects of their followers' world. This study tested the relationships of vision, a common theme to all of the prominent new leadership theories, to the emotion-focused affective commitment (AC) versus the cognitionfocused continuance commitment (CC) to the organ.